Bots conversacional en la información política desde la experiencia de los usuarios: Politibot - Sánchez-Gonzales, Hada-M.; Sánchez-González, María (Communication & Society, 2020)
The production and distribution of news is changing. At the same time, the relationship between journalism and artificial intelligence systems is becoming stronger. Within this context, conversational bots have appeared, which are software applications that distribute personalised content (Al Johri et al., 2016) through social networks, online instant messaging apps, and mobile devices. This research presents a case study on the conversational political news bot known as Politibot, which is a pioneering, successful Spanish project that emerged during the 2016 election campaign. The study analyses users’ perceptions of the bot as a news and conversational tool based on their experience of use. An experimental methodology has been used in combination with other qualitative and quantitative research techniques (documentary analysis, direct observation, registration forms, as well as pre-test and post-test by means of questionnaires). The results show widespread acceptance in terms of reliability, comprehension, and the format regarding the information received from the bot, as well as its immediacy and customisation. However, the possibility of interacting with bots is still limited, which is also true of the case under study herein. La producción y distribución de noticias está cambiando a la vez que se hace más estrecha la relación entre periodismo y los sistemas de inteligencia artificial. En este contexto, aparecen los bots conversacionales, aplicaciones que distribuyen contenido personalizado (Al Johri et al., 2016) en las redes sociales y en las apps de mensajería instantánea vía online y a través de los dispositivos móviles. La presente investigación plantea un estudio de caso sobre el bot conversacional de información política Politibot, proyecto español pionero y de éxito surgido durante la campaña electoral de 2016. Se analiza la percepción que los usuarios tienen del bot como herramienta informativa y conversacional tras su experiencia de consumo. Se hace uso de una metodología experimental combinada con otras técnicas cualitativas y cuantitativas de investigación (análisis documental, observación directa y ficha de registro, pre-test y pos-test por medio de cuestionarios). Los resultados muestran gran aceptación en cuanto a la fiabilidad, comprensión y formato de la información recibida por el bot, así como a su inmediatez y personalización. Sin embargo, las posibilidades de interacción con bots, como el caso analizado, son aún limitadas.